Method for producing alloy ingot - KUSAMICHI TATSUHIKO; NAKAYAMA JUMPEI (2013)
Disclosed is a method for producing alloy ingot including: a step of: charging alloy starting material into a cold crucible in a cold-crucible induction melter, and forming melt pool of the alloy starting material by induction heating in inert gas atmosphere; a step of continuing the induction heating and adding first refining agent to the melt pool, and then reducing the content of at least phosphorus from among impurity elements present in the melt pool; and a step of forming alloy ingot by solidifying the melt, the phosphorus content of which has been reduced. The first refining agent is mixture of metallic Ca and flux, where the flux contains CaF2 and at least one of CaO and CaCl2. The weight proportion of the sum of CaO and CaCl2 with respect to CaF2 ranges from 5 to 30 wt % and the weight proportion of metallic Ca with respect to the melt pool is 0.4 wt % or greater.